Self-Concept, Family Roles, Knowledge and Information Resource on Dating Violence Prevention Behaviors: A Cross-sectional Study using Smart PLS Software - Muriana, Eviyati Aini; Lestari, Nur Cahyani Ari; Nurhayani, Nurhayani; Zulhijriani, Zulhijriani (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Gender aspects hold an important role in forming strategies for teenagers to get their acceptance in the neighborhood, especially at the beginning of teenage life development. One of the negative conditions if the development cannot be well developed is violence in dating. Aims: The aim of this study was to determine the direct and indirect effects, as well as the amounts of resources, role of family, knowledge, and self-concept, against the prevention of violence in dating at SMK Wijaya Kusuma in South Jakarta in 2016. Methods: This study used a cross-sectional design. The population consisted of students in the 9th and 10th grades, and 65 students were selected as respondents. This study used a structure equation model as an analysis method using Smart PLS 2.0 and SPSS 18.0. Results: The hypothesis testing produced findings that all independent variables have an effect on dependent variables: resources by 16.14%, role of family by 11.38%, knowledge by 15.95%, and self-concept by 20,38%. The self-concept variable was the dominant factor in influencing the preventive behavior of violence in dating. Model analysis results can explain 95% of the diversity of this research and the ability to assess the phenomenon, while 5% are described by other components that do not exist in this study. Conclusion: In sum, there was an influence-relationship between resources, the role of family, knowledge, and self-concept in preventing violence in dating. We suggest that schools should provide education about violence prevention strategies so that they are well-informed about violence in dating. Received: 07 December 2023, Reviewed: 12 December 2023, Revised: 06 January 2024, Accepted: 14 January 2024.